Maternal Employment, Family Functioning, and Preterm Infant Development at 9 and 12 Months - Youngblut, JoAnne M. (1993)
The purpose of this study was to investigate the effects of maternal employment on child development and family functioning for families with preterm infants. Data were collected in the family’s home (N = 67) when the infant was 3, 9, and 12 months of age. Maternal employment at 3 months had little effect on 9- and 12-month child mental or psychomotor development or on family cohesion, adaptability, or satisfaction. Maternal employment attitude/behavior consistency was a significant predictor of psychomotor development. Choice in the employment decision at 3 months was positively related to both mental and psychomotor development at 9 and 12 months for nonemployed mothers.